Coarsening Evolution of γ′ Phase and Failure Mechanism of Co-Ni-Al-Ti-Based Superalloys During Isothermal Aging - Zhang, Xuming; Shang, Hang; Gao, Qiuzhi; Ma, Qingshuang; Zhang, Hailian; Li, Huijun; Sun, Linlin (Frontiers in Materials, 2022)
Novel Co-based superalloys, as potentially ideal aero-engine hot section materials, have higher temperature bearing capacity and more excellent oxidation resistance than Ni-based superalloys. Coarsening evolution of γ' phase and failure mechanism of Co-Ni-Al-Ti-based superalloys during isothermal aging process at 1073K were investigated using multiple characterizations and testing methods. The results show that, γ' phase is uniformly distributed on γ phase matrix, and coarsening with increase in isothermal aging time, in which results decrease in maximum tensile strength. Furthermore, Mo element is preferred to distribute in γ' phase and provides stronger solution strengthening effect than Cr element, which determines more excellent mechanical properties of 2Mo superalloy than that of 2Cr superalloy. Coarsening rate of γ' phase in 2Cr superalloy is significantly higher than that in 2Mo superalloy. Grain boundary failure is dominant in isothermal aging, and the cracks nucleate and expand along vertical direction of loading stress on grain boundary. The current work suggests that grain boundary failure caused by coarsening of γ' phase and formation of γ'-precipitate depleted zone (PDZ) near grain boundary during aging controls the deterioration of mechanical properties in Co-Ni-Al-Ti-based superalloys.